Aluminum-based microporous sound-absorbing structure and forming method thereof

CN122888940APending Publication Date: 2026-10-09CHINA RAILWAY DESIGN GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610663670.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-14
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0005]为解决现有传统阻性吸声材料粉化污染、安装复杂、耐候性差,以及现有微孔吸声结构吸声频带窄、结构强度不足、加工精度低、复合可靠性差等技术问题,本发明提供一种铝基微孔吸声结构及其成型方法

Benefits of technology

[0035]1.本发明采用全铝基材料体系,无任何多孔纤维填充,从源头杜绝粉尘污染与霉变问题,环保等级达E0级,且全材料可100%回收再利用,同时铝基结构自身具备足够强度,安装时无需额外龙骨、网罩等固定结构,可直接采用卡扣、螺栓等简易方式安装,大幅简化施工流程,有效解决了传统阻性吸声材料粉化污染、不可降解、安装复杂及维护成本高的核心弊端。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122888940A_ABST
    Figure CN122888940A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of architectural acoustics materials, and particularly relates to an aluminum-based micro-porous sound absorption structure and a forming method thereof. The forming method comprises the following steps: substrate processing; film processing; composite forming; post-processing; and performance detection. The aluminum-based micro-porous sound absorption structure comprises an aluminum substrate and an aluminum film, the aluminum substrate is provided with a first circular hole array; the aluminum film is provided with a second micro-gap array, the aluminum film is covered and fixed on the upper surface of the aluminum substrate through an aluminum-based composite process, and the first circular hole array and the second micro-gap array are one-to-one vertically aligned. Through the cooperative design of the circular hole array and the micro-gap array, combined with the vibration damping characteristics of the aluminum film, the three sound absorption mechanisms of micro-porous resonance, micro-gap friction and film damping are constructed, the excellent performance of the sound absorption coefficient being greater than or equal to 0.75 in the wide frequency range of 500-2000 Hz and the low-frequency sound absorption coefficient being greater than or equal to 0.9 at 500 Hz is realized, the sound absorption frequency band of the traditional micro-porous structure is widened by more than 40%, and the mainstream noise frequency bands such as traffic noise and industrial noise are effectively covered.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of architectural acoustic materials technology, specifically relating to an aluminum-based microporous sound-absorbing structure and its molding method, which is suitable for scenarios with stringent requirements for noise control, fire safety, and environmental performance, such as rail transit, public buildings, education and medical facilities, and industrial plants. Background Technology

[0002] Noise pollution has become a significant issue affecting both living environments and industrial production. Traditional resistive sound-absorbing materials widely used in noise control primarily consist of porous materials such as rock wool, glass wool, and polyester fiber cotton. While these materials possess some sound absorption properties, they suffer from several insurmountable drawbacks: First, they generally exhibit weak low-frequency sound absorption performance, with absorption coefficients below 500Hz often below 0.3, failing to meet the demands of noise control in complex environments. Second, prolonged exposure to humid, high-temperature, or vibrating environments can lead to mold growth, powdering, and dust pollution, posing a health hazard, making them particularly unsuitable for complex conditions such as rail transit and industrial plants. Third, porous materials are often non-degradable, causing environmental pollution upon disposal, and some contain harmful additives. Fourth, installation is complex; these materials are soft and lack structural strength, requiring additional support and enclosure structures such as joists and mesh covers during installation. This not only increases construction costs and time but also carries the risk of detachment due to insecure installation, resulting in high subsequent maintenance costs.

[0003] To address the shortcomings of traditional resistive sound-absorbing materials, microporous sound-absorbing structures have emerged. With advantages such as no need for porous materials, light weight, excellent weather resistance, and no secondary pollution, they have gradually become a research hotspot and application trend in noise control. Microporous sound-absorbing structures achieve sound absorption by processing tiny holes in a material, utilizing sound wave resonance and viscous friction to dissipate sound energy. This effectively overcomes problems such as pulverization, pollution, and complex installation associated with traditional porous materials. However, existing microporous sound-absorbing structures still face significant technical bottlenecks: First, the effective sound absorption frequency band of a single-layer microporous structure typically only covers 1-2 octaves, making it difficult to achieve efficient control of broadband noise. While multi-layer composite structures can extend the frequency band, they also lead to structural complexity and increased costs. Second, to balance sound absorption performance and processing difficulty, existing microporous structures often employ thin-plate designs, resulting in insufficient structural rigidity and susceptibility to deformation under external forces, making them unsuitable for environments with strong vibrations and high impacts, such as industrial plants and rail transportation. Third, the processing technology is complex and precision is difficult to control. Traditional microporous processing often employs stamping, mechanical drilling, or ordinary laser cutting. Stamping easily leads to burrs on the hole edges and uneven hole diameters, mechanical drilling is inefficient, and ordinary laser cutting has problems such as a large heat-affected zone and excessive micropore width tolerances. Especially for the processing of micro-gaps below 0.5mm, existing processes are difficult to achieve standardized mass production.

[0004] To address the shortcomings of existing microporous sound-absorbing structures, the industry has undertaken numerous attempts. Some solutions employ multi-layered microporous plates with varying pore sizes to expand the sound absorption bandwidth through multi-frequency resonance. However, these structures suffer from increased weight, installation difficulty, and rising costs, and the interlayer bonding reliability is insufficient, leading to delamination over long-term use. Other solutions optimize the microporous plate material by using a composite substrate of metal and non-metal, attempting to balance strength and sound absorption performance. However, the significant differences in the thermal expansion coefficients of different materials can easily generate interfacial stress in environments with temperature variations, causing structural cracking. Furthermore, the introduction of non-metallic materials reduces the fire resistance and recyclability of the materials. Still other solutions attempt to optimize the sound absorption frequency band by adjusting the arrangement and pore size parameters of the micropores, but this lacks coordinated design with processing technology and structural strength, often resulting in compromises. In addition, existing composite processes for microporous structures mostly use ordinary adhesive bonding, which suffers from insufficient fire resistance, poor aging resistance, and low peel strength, making it difficult to meet the stringent safety requirements of public buildings and rail transit systems. In summary, existing microporous sound-absorbing structures still have many shortcomings in terms of broadband sound absorption, structural strength, processing precision, environmental recyclability, and composite reliability. There is an urgent need for an innovative sound-absorbing structure that can comprehensively solve the above problems. Summary of the Invention

[0005] To address the technical problems of existing traditional resistive sound-absorbing materials, such as pulverization and pollution, complex installation, and poor weather resistance, as well as existing microporous sound-absorbing structures, such as narrow sound absorption bandwidth, insufficient structural strength, low processing precision, and poor composite reliability, this invention provides an aluminum-based microporous sound-absorbing structure and its molding method.

[0006] The present invention adopts the following technical solution:

[0007] A method for forming an aluminum-based microporous sound-absorbing structure includes the following steps:

[0008] S1. Substrate processing: The first array of circular holes is processed on the 3-series aluminum alloy sheet using CNC drilling technology to form an aluminum substrate. After processing, the surface of the aluminum substrate is polished.

[0009] S2. Thin film processing: A second micro-slit array is processed on an aluminum thin film using ultraviolet laser processing equipment, and the laser power is adjusted according to the micro-slit width requirements.

[0010] S3. Composite molding: The aluminum-based composite process is used to precisely bond and fix the aluminum film to the aluminum substrate and achieve metallurgical bonding, so that the second slit array and the first circular hole array are precisely aligned in position.

[0011] S4. Post-treatment: Perform surface anti-corrosion treatment on the composite structure to form an anodized anti-corrosion layer and / or an anti-oxidation coating on the surface;

[0012] S5. Performance Testing: Perform sound absorption coefficient testing on the finished product. If the sound absorption coefficient test does not reach the expected value, perform geometric dimension testing on the first circular hole array of the aluminum substrate and / or the second micro-slit array of the aluminum film. Compare the measured dimensions with the verified target tolerance. Based on the direction and magnitude of the dimensional deviation, reverse the adjustment of the CNC drilling process parameters and / or ultraviolet laser processing parameters to correct the processing error, so that the geometric characteristics of the circular holes and micro-slits are restored to the predetermined tolerance range. Then, repeat step S3 and subsequent steps until the sound absorption coefficient is qualified.

[0013] In the above technical solution, in steps S1 and S2, a CCD vision positioning system is used to align the center position of the first circular hole array with a positioning accuracy of ≤0.08mm to ensure the positional accuracy of processing and stacking.

[0014] In the above technical solution, step S3, the aluminum-based composite process is a hot-rolled composite method, which includes the following steps:

[0015] S301. The bonding surfaces of the aluminum substrate and the aluminum film are subjected to plasma activation treatment.

[0016] S302. By using positioning pins and alignment marks, the aluminum film and aluminum substrate are precisely stacked to form a composite, with a positioning error ≤0.1mm.

[0017] S303. The composite material is fed into a hot rolling mill and rolled at a temperature of 350-450°C and a pressure of 20-40 MPa to achieve metallurgical bonding between the two metal layers. The peel strength of the interface after bonding is ≥1.5 MPa. The hot rolling temperature T and rolling pressure P are complementary. Preferably, when T is 350-380°C, P is 35-40 MPa; when T is 380-420°C, P is 28-35 MPa; and when T is 420-450°C, P is 20-28 MPa. This ensures that the oxide film at the interface is fully broken down and metallurgically bonded, while avoiding damage to the microporous structure due to overheating or overpressure.

[0018] In the above technical solution, the aluminum-based composite process is an adhesive bonding method. The adhesive used is selected from one or more of the following: fire-resistant Class A inorganic silicate adhesive, ceramic-based adhesive, or aluminum-based composite adhesive. The adhesive thickness is 0.03-0.08mm, and the temperature resistance after bonding is ≥600℃.

[0019] In the above technical solution, in step S4, the side of the aluminum substrate facing away from the aluminum film is anodized to form an anodized anti-corrosion layer. The anodizing process is sulfuric acid anodizing, the oxide layer thickness is 10-15μm, and the anti-corrosion level reaches C3 or above. The surface of the aluminum film is provided with an anti-oxidation coating with a thickness of 5-10μm. The anti-oxidation coating is prepared by vacuum coating process and the material is aluminum oxide or aluminum nitride.

[0020] The second objective of this invention is to provide an aluminum-based microporous sound-absorbing structure prepared by the molding method described above, comprising:

[0021] An aluminum substrate, which is a 3-series aluminum alloy substrate, has a first circular hole array that penetrates the thickness direction.

[0022] An aluminum thin film, which is an aluminum alloy thin film adapted to an aluminum substrate, has a second micro-slit array extending through the thickness direction. The aluminum thin film is covered and fixed to the upper surface of the aluminum substrate by an aluminum-based composite process. The center of each circular hole in the first circular hole array is aligned vertically with the center of each micro-slit in the second micro-slit array. The length of each micro-slit is not greater than the difference between the spacing and diameter of the corresponding circular hole in the first circular hole array that is aligned with it. In a wide frequency range of 500-2000Hz, a double-peak coupling effect is generated between the first circular hole array and the second micro-slit array, with a sound absorption coefficient ≥0.75.

[0023] In the above technical solution, the thickness of the aluminum substrate is 2-5mm, the thickness of the aluminum film is 0.1-0.3mm, and the arrangement spacing of the first circular hole array is equal to the arrangement spacing of the second micro-slit array.

[0024] In the above technical solution, the circular holes in the first circular hole array are periodically distributed in a square lattice, the diameter of the circular holes in the first circular hole array is 2-4 mm, and the spacing between adjacent circular holes is 5-8 mm.

[0025] In the above technical solution, the microslits in the second microslit array are arranged in parallel, the width of the microslits in the second microslit array is 0.2-0.8mm, and the length is 1.2-1.8 times the diameter of the circular holes in the first circular hole array; the second microslit array is formed by ultraviolet laser processing, and material removal is achieved during the processing, the laser spot diameter is ≤0.05mm, the processing speed is 10-30mm / s, and the microslit width tolerance is ≤±0.05mm.

[0026] The sound absorption coefficient meets the following requirements: ≥0.75 in a wide frequency range of 500-2000Hz, with a sound absorption coefficient ≥0.9 at 500Hz, and a noise reduction coefficient (NRC) ≥0.75;

[0027] sound absorption coefficient The calculation formula is:

[0028]

[0029] In the formula:

[0030]

[0031]

[0032] in, =1.84e -5 Pa·s is the air viscosity coefficient; t is the aluminum film thickness, in meters. denoted as the hydraulic diameter; a and b are the width and length of the microslit, respectively. The open area ratio is equal to the ratio of the open area to the total area. , is a dimensionless constant; Where f is the angular frequency, and f is a number ranging from 20 to 8000 Hz; air density; denoted as the speed of sound in air; D is the depth of the back cavity of the microporous sound-absorbing structure in meters; r is the acoustic resistance; and m is the acoustic mass.

[0033] The aluminum-based microporous sound-absorbing structure of this invention comprehensively solves many defects of traditional sound-absorbing materials and existing microporous structures through the synergistic innovation of all-aluminum-based material design, precise processing technology and reliable composite technology. It has multiple advantages such as wide-band sound absorption, high strength, strong weather resistance, environmental recyclability and convenient installation.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] 1. This invention uses an all-aluminum-based material system without any porous fiber filling, eliminating dust pollution and mold problems from the source. It achieves an environmental protection level of E0, and all materials are 100% recyclable. At the same time, the aluminum-based structure itself has sufficient strength, and no additional keel, mesh cover or other fixing structure is required during installation. It can be installed directly using simple methods such as buckles and bolts, which greatly simplifies the construction process and effectively solves the core drawbacks of traditional resistive sound-absorbing materials, such as powdering pollution, non-degradability, complex installation and high maintenance costs.

[0036] 2. This invention, through the synergistic design of circular hole array and micro-slit array, combined with the vibration damping characteristics of aluminum film, constructs a triple sound absorption mechanism of micro-hole resonance, micro-slit friction, and film damping, achieving excellent performance with a sound absorption coefficient ≥0.75 in a wide frequency range of 500-2000Hz and a low-frequency sound absorption coefficient ≥0.9 at 500Hz. Compared with traditional micro-hole structures, the sound absorption frequency band is widened by more than 40%, effectively covering mainstream noise frequencies such as traffic noise and industrial noise, and successfully breaking through the acoustic performance bottleneck of narrow sound absorption frequency band of existing micro-hole sound absorption structures.

[0037] 3. This invention uses a three-series aluminum alloy substrate and a suitable aluminum film. Through hot rolling metallurgy bonding or composite with Class A adhesive, the interfacial peel strength is ≥1.5MPa, the overall compressive strength of the structure is ≥2.5MPa, and the impact resistance meets the relevant requirements of GB / T14152-2021. At the same time, the synergistic effect of the anodized anti-corrosion layer on the back of the substrate and the anti-oxidation coating on the surface of the film makes the corrosion resistance level reach C3 or above, the weather resistance range covers -40℃ to 600℃, and the service life is as long as 25 years or more. This significantly improves the structural strength and adaptability of the sound-absorbing structure to complex environments, and solves the problems of insufficient strength and poor weather resistance of existing microporous structures.

[0038] 4. This invention employs ultraviolet laser material removal processing for the second micro-gap, combined with a CCD vision positioning system to achieve a positioning accuracy of ≤0.08mm and a micro-gap width tolerance of ≤±0.05mm, with a processing speed of 10-30mm / s. Simultaneously, the substrate circular hole is drilled using CNC drilling technology to ensure a surface roughness Ra≤0.8μm and burr-free hole edges. This improves the accuracy by an order of magnitude compared to traditional tool engraving and ordinary laser processing, realizing precise processing and mass production, and solving the problems of low accuracy, poor efficiency, and difficulty in mass application of existing micro-hole processing.

[0039] 5. This invention combines all-aluminum base materials with Class A fire-retardant adhesive to achieve a fire rating of A2, meeting the highest safety standard for combustion performance of building materials in GB 8624-2012. Simultaneously, the structural thickness is only 2.1-5.3mm, and the weight is ≤8kg / ㎡, making it suitable for various installation scenarios such as ceilings and walls. Furthermore, the surface can be anodized, painted, or otherwise decorated as needed, achieving an integration of acoustic function and decorative effect, thus balancing the safety performance and practical value of the sound-absorbing structure.

[0040] In addition, the inventive step evidence for this invention is also reflected in the following important aspects:

[0041] 1. The aluminum-based microporous sound-absorbing structure provided by this invention adopts an all-metal single-material system, eliminating the need for filling with porous fiber materials such as rock wool and glass wool, which can significantly reduce product transportation and on-site installation costs. Compared with the traditional sound-absorbing cotton + perforated aluminum plate structure, this solution reduces material costs by approximately 15%-20%, improves construction efficiency by over 40%, and reduces overall life-cycle costs by approximately 30%. This product has significant advantages in scenarios with extremely high requirements for fire resistance, environmental protection, and durability, such as rail transit stations, large public buildings, and industrial plants. Furthermore, the all-aluminum material is 100% recyclable, with a residual value more than 10 times higher than traditional sound-absorbing materials, possessing outstanding commercial and environmental value.

[0042] 2. Currently, there are no sound-absorbing structures or related molding methods that can simultaneously meet the requirements of "all-aluminum base, fiber-free filling, precise coupling of circular holes and micro-slits in a dual array, wide bandwidth and high absorption, Class A fire resistance, and 100% recyclability," both domestically and internationally. Existing microporous sound absorbers either have narrow bandwidths or rely on multi-layer composites or non-metallic fillings, leading to decreased fire resistance and recyclability. This invention proposes for the first time to combine a large-diameter circular hole array on an aluminum alloy substrate with a micro-slit array processed by ultraviolet laser on an aluminum thin film, centered vertically. Utilizing an equal-length covering design where the length of the micro-slits equals the diameter of the circular holes, a series acoustic quality system is constructed within a single structural component, achieving dual-peak coupling and high sound absorption in a wide frequency range of 500-2000 Hz. This fills the technological gap in the engineering manufacturing of metal-based wideband resonant-friction coupled sound absorbers and provides a new technological route that combines precise dimensional control with reliable metallurgical integration.

[0043] 3. Currently, the core technical challenge that has plagued the field of architectural acoustics for decades is how to simultaneously achieve excellent low-frequency sound absorption, wide-bandwidth high absorption, high structural strength, Class A fire resistance, full-life-cycle environmental friendliness, and convenient installation within a single thin-layer structure. Traditional porous fiber materials cannot meet the requirements for strength, fire resistance, and environmental protection; single-layer micro-perforated panels have a narrow sound absorption band; and multi-layer composite structures bring delamination risks and significantly increased costs. The technical solution of this invention, through an all-aluminum-based material system, the correlation between the size and position of circular holes and micro-slits, hot-rolled metallurgical bonding or inorganic Class A adhesive, and differentiated anti-corrosion treatment on each surface, achieves all of the above performance indicators in the same structure for the first time. In particular, the sound absorption coefficient reaches above 0.9 at 500 Hz and the sound absorption coefficient across the entire 500-2000 Hz band is not less than 0.75, solving the long-standing technical problem that thin-layer metal structures cannot achieve wide-bandwidth, high-efficiency sound absorption.

[0044] 4. The following technical biases have long existed in this field: First, it is believed that metal microporous / microslit sound absorbers, due to their insufficient damping, must introduce porous fibers or high-damping polymer layers to achieve broadband sound absorption, resulting in complex structures and loss of the advantages of all-metal recycling; second, it is believed that micron-level slit processing can only rely on high-cost, low-efficiency precision scribing or die stamping, making it impossible to achieve wide-area, high-consistency mass production; third, it is believed that it is difficult to simultaneously meet the requirements of 600℃ temperature resistance and Class A fire resistance. This invention, without any fiber filling, completely breaks through the above technical biases by using ultraviolet laser cold processing to remove slits, hot rolling metallurgical bonding or inorganic Class A adhesive bonding, and a faceted anti-corrosion scheme of anodizing the back of the substrate and vacuum coating on the thin film surface. It fully demonstrates that the all-aluminum-based microporous-microslit coupled structure itself possesses excellent broadband sound absorption, ultra-wide weather resistance, and high-strength durability, and is feasible for mass production. Attached Figure Description

[0045] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this disclosure and, together with the description, serve to explain the principles of this disclosure;

[0046] Figure 1 This is a schematic diagram of the front structure of the aluminum-based microporous sound-absorbing structure in this invention;

[0047] Figure 2 This is a cross-sectional view of the aluminum-based microporous sound-absorbing structure in this invention.

[0048] Figure 3 This is a flowchart of the molding method of the aluminum-based microporous sound-absorbing structure in this invention;

[0049] Figure 4 This is a field test diagram of the sound absorption coefficient in the reverberation chamber in Example 1;

[0050] Figure 5 This is the sound absorption coefficient curve at the center frequency of 1 / 3 octave band in Example 1;

[0051] Figure 6 This is a field test diagram of the reverberation time test in Example 2;

[0052] Figure 7 This is a graph showing the reverberation time changes before and after applying the aluminum-based microporous sound-absorbing structure in Example 2.

[0053] In the figure: 1-aluminum substrate; 2-aluminum thin film; 3-first circular hole array; 4-second micro-slit array; 5-anodized anti-corrosion layer; 6-anti-oxidation coating. Detailed Implementation

[0054] To make the above-mentioned objects, features, and advantages of the present invention more apparent and understandable, specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings. Many specific details are set forth in the following description to provide a thorough understanding of the present invention. However, the present invention can be practiced in many other ways different from those described herein, and those skilled in the art can make similar modifications without departing from the spirit of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0055] The present invention will be further described in detail below with reference to specific embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention.

[0056] Example 1:

[0057] Substrate processing: 3003-H12 aluminum alloy sheet (yield strength ≥120MPa) is selected. The first circular hole array is processed by CNC drilling machine. The diameter of the circular hole is 3mm and the spacing between adjacent circular holes is 6mm. It is distributed in a square lattice. The substrate thickness is 3mm. After processing, mechanical grinding and chemical polishing are used to remove burrs and oxide layers from the hole edges.

[0058] Thin film processing: 3003 aluminum film with a thickness of 0.2mm was selected. The second micro-slit array was processed using an ultraviolet laser processing machine (model: IPGYLP-15). Laser parameters: spot diameter 0.04mm, processing speed 20mm / s, laser power 10W. The center of the circular hole was aligned with a CCD vision positioning system with a positioning accuracy of 0.06mm. The width of the micro-slits was 0.5mm and the length was 4mm (1.33 times the diameter of the circular hole). The micro-slits were arranged in parallel with a spacing of 6mm.

[0059] Composite forming: The hot rolling composite method is adopted. First, the bonding surface of the substrate and the film is subjected to plasma activation treatment (argon atmosphere, power 500W, time 30s). The film and the substrate are precisely stacked by the cooperation of positioning pins and alignment marks, with a positioning error of 0.08mm. The composite is fed into the hot rolling mill and rolled in a single pass at a temperature of 380°C and a pressure of 30MPa, with a rolling speed of 1.5m / min. The peel strength of the interface after composite is 1.8MPa.

[0060] Post-processing: The back side of the substrate is anodized with sulfuric acid at a temperature of 18°C, a current density of 1.2A / dm², and an oxidation time of 40 min to form an anodized anti-corrosion layer with a thickness of 12μm; the surface of the film is coated with an alumina anti-oxidation coating using a vacuum deposition process at a temperature of 150°C, a vacuum degree of 5×10⁻³Pa, and a coating thickness of 8μm.

[0061] Performance testing: According to GB / T 20247-2006, the sound absorption coefficient was tested in the reverberation chamber: 0.90 at 500Hz, 0.85 at 1000Hz, and the noise reduction coefficient NRC=0.75; according to GB / T 1408.1-2021, the interfacial peel strength was tested at 1.8MPa; according to GB 8624-2012, the fire resistance rating was tested as A2; according to GB / T 10125-2021 "Artificial Atmosphere Corrosion Test - Salt Spray Test", after 1000 hours of neutral salt spray test, no rust was found on the surface.

[0062] like Figure 5 As shown, in this embodiment, through the synergistic design of the circular hole array and the micro-slit array, combined with the vibration damping characteristics of the aluminum film, a triple sound absorption mechanism of micro-hole resonance, micro-slit friction, and film damping is constructed, achieving excellent performance with a sound absorption coefficient ≥0.75 in a wide frequency range of 500-2000Hz and a low-frequency sound absorption coefficient ≥0.9 at 500Hz, which is more than 40% wider than the sound absorption frequency band of traditional micro-hole structures.

[0063] Example 2:

[0064] Substrate processing: 3004-H14 aluminum alloy sheet (yield strength ≥140MPa) is selected. The first circular hole array is processed by CNC drilling. The diameter of the circular hole is 4mm, the spacing between adjacent circular holes is 7mm, and the substrate thickness is 4mm. After processing, it is polished to achieve a surface roughness Ra=0.7μm.

[0065] Thin film processing: 3004 aluminum thin film with a thickness of 0.25mm is selected. Ultraviolet laser processing parameters: spot diameter 0.05mm, processing speed 15mm / s, laser power 12W; CCD vision positioning, micro-slit width 0.6mm, length 6mm (1.5 times the diameter of the circular hole), and spacing 7mm.

[0066] Composite molding: An adhesive bonding method is adopted, using inorganic silicate adhesive (model: WD-801), which is coated onto the substrate surface by screen printing, with an adhesive thickness of 0.05mm; after the film and substrate are precisely stacked, they are placed in an autoclave and cured at 120°C and 0.5MPa for 60 minutes, and the bonded film can withstand a temperature of 650°C.

[0067] Post-processing: The thickness of the anodized anti-corrosion layer on the back of the substrate is 14μm, and the thickness of the aluminum nitride anti-oxidation coating on the surface of the film is 7μm.

[0068] Performance testing: Reverberation chamber test results: 500Hz sound absorption coefficient 0.91, 1000Hz sound absorption coefficient 0.83, 2000Hz sound absorption coefficient 0.76, noise reduction coefficient NRC=0.79; interfacial peel strength 1.6MPa; fire resistance rating A2; no rust after 1000 hours of salt spray test.

[0069] The above-described products have been piloted in the HVAC equipment control room of a Tianjin station and the waiting hall of a Zhanjiang station. During installation, a snap-on fixing method is used, eliminating the need for additional keel support, thus improving construction efficiency by 50% compared to traditional sound-absorbing materials. After application, such as... Figure 6-7 As shown, the average reverberation time of the operating room at a certain station in Tianjin was reduced from 1.0s to 0.7s in the 500-1000Hz range, and the noise level of the waiting hall at a certain station in Zhanjiang was reduced from 68dB(A) to 55dB(A), meeting the requirements of the "Code for Sound Insulation Design of Civil Buildings" (GB 50118-2010) and gaining high recognition from the owners.

[0070] Example 3: Mechanism Verification and Comparison

[0071] To verify the nonlinear superposition effect of the synergistic coupling of the circular hole array and the micro-slit array in this invention, the following comparative tests were conducted.

[0072] Comparative Example 1 (Single-layer microporous plate): Only the aluminum substrate (thickness 3mm, diameter of round holes 3mm, spacing 6mm, square lattice distribution) described in Example 1 is used, without composite aluminum film.

[0073] Comparative Example 2 (Single-layer micro-slit plate): Only the aluminum film described in Example 1 (thickness 0.2 mm, micro-slit width 0.5 mm, length 4 mm, parallel arrangement, spacing 6 mm) is used, without composite aluminum substrate.

[0074] Comparative Example 3 (non-centered lamination): The same aluminum substrate and aluminum film as in Example 1 were used, but during the composite molding process, the center of the micro-gap was intentionally offset from the center of the circular hole by more than 1.5 mm.

[0075] Comparative Example 4 (outside the parameter range): The microslit width was increased to 1.2 mm (outside the range of 0.2-0.8 mm), and the other parameters were the same as in Example 1.

[0076] The above comparative samples were all tested for sound absorption coefficient in the same reverberation chamber according to GB / T 20247-2006, and the results are shown in the table below.

[0077] Table 1: Sound Absorption Coefficient Test Data Table

[0078] Comparative Example 1 (microporous substrate only) 0.08 0.12 0.15 0.05 Comparative Example 2 (microslit film only) 0.55 0.50 0.42 0.35 Comparative Examples 1 and 2: Arithmetic Means (Theoretical Simple Superposition) 0.32 0.31 0.29 0.20 Example 1 0.90 0.85 0.78 0.75 Comparative Example 3 (Non-centered overlapping) 0.62 0.68 0.60 0.52 Comparative Example 4 (outside the parameter range, slit width 1.2mm) 0.58 0.65 0.63 0.48

[0079] As can be seen from the data in Table 1:

[0080] (1) The sound absorption coefficient of Comparative Example 1 (microporous substrate only) is extremely low (NRC only 0.05), which is in complete agreement with the prediction of the sound absorption theory of micro-perforated plates. The pore diameter of 3 mm far exceeds the requirements of micropores in the sub-millimeter range. When the air column vibrates, there is almost no viscous friction loss, and the sound energy is only weakly reflected rather than absorbed. This result shows that a single large-diameter circular hole aluminum plate does not have an effective sound absorption function.

[0081] (2) The measured noise reduction coefficient (NRC) of Embodiment 1 of the present invention is 0.75, which is significantly higher than the arithmetic mean of each comparative example. Specifically, it is 275% higher than the arithmetic mean (0.20) of the microporous substrate and the microslit film tested separately, far exceeding the effect of simple linear superposition of the two. This strongly proves that the broadband high sound absorption performance of the present invention is not a simple superposition of two single-layer structures, but rather stems from the synergistic coupling effect generated after the precise alignment of the circular hole array and the microslit array. The microslit array not only provides frictional sound absorption itself, but also fundamentally changes the acoustic boundary conditions of the air column in the original large hole structure, transforming the "acoustic inert" large hole into an organic component of the high-efficiency resonant cavity.

[0082] (3) In terms of acoustic mechanism, this structure forms a series acoustic mass-acoustic resistance system of "large hole resonant cavity + micro-slit friction layer". Although the circular hole (diameter 2-4mm) has extremely low acoustic resistance, its air column acts as an acoustic mass element, connected in series with the concentrated acoustic resistance and additional acoustic mass formed by the micro-slit. When the centers of the two are precisely aligned, the resonance of the circular hole air column is effectively damped by the high acoustic resistance of the micro-slit, forming a strong and wide low-frequency resonance peak (around 500Hz); at the same time, the micro-slit itself generates a second resonance peak at a higher frequency (about 1600Hz). The two peaks are connected in series through the acoustic path to form a complementary superposition, realizing a wide sound absorption platform of 500-2000Hz. Comparative Example 3 (non-aligned superposition) destroys the continuous acoustic path of hole-slit, and the resonance peak degenerates and separates, with NRC decreasing from 0.75 to 0.52, which fully proves that precise spatial alignment is the decisive condition for stimulating this coupling effect; otherwise, the coupling effect is significantly weakened.

[0083] (4) In Comparative Example 4, when the microslit width was increased to 1.2 mm, the viscous boundary layer of air inside the slit could not develop sufficiently, resulting in a significant decrease in acoustic impedance. This prevented the slit from providing sufficient damping matching for the circular hole resonance, causing the low-frequency absorption coefficient to drop from 0.90 to 0.58 and the NRC to drop from 0.75 to 0.48. This indicates that the microslit width must be controlled within the range of 0.2-0.8 mm and designed in conjunction with parameters such as the circular hole diameter and film thickness using impedance matching theory to achieve the optimal sound absorption effect.

[0084] Example 4: Verification of Key Parameter Correlation

[0085] This embodiment verifies the impact of the ratio of micro-gap length to circular hole diameter and the correlation between hot rolling temperature and pressure on sound absorption performance and structural reliability.

[0086] 4.1 Verification of the optimal ratio of micro-slit length to circular hole diameter

[0087] The diameter of the fixed circular hole was 3 mm (same as in Example 1), and different micro-slit lengths were set: 3.0 mm (ratio 1.0), 4.0 mm (ratio 1.33), 5.4 mm (ratio 1.8), and 6.5 mm (ratio 2.17). The other parameters were the same as in Example 1. The sound absorption coefficients of each sample were tested in a reverberation chamber, and the results are shown in the table below.

[0088] Table 2: Verification Data Table of Key Parameter Correlationships

[0089] 3.0mm 1.0 0.75 0.80 0.60 The interval between the low-frequency resonant peak and the mid-frequency peak is too narrow, and the peak-to-valley ratio is not coordinated. 4.0mm 1.33 0.90 0.85 0.75 The dual-peak coupling is optimal, resulting in the widest bandwidth. 5.4mm 1.8 0.88 0.82 0.72 Mid-frequency sound absorption decreased slightly, but remained within the optimal range. 6.5mm 2.17 0.78 0.76 0.65 Beyond the optimal range, high-frequency sound absorption decreased significantly.

[0090] The results show that when the length-to-diameter ratio is 1.33 (Example 1), the sound absorption bandwidth is the widest, the acoustic impedance matching is optimal, the amplitudes of the two resonance peaks are balanced, and the spacing is reasonable, achieving the widest effective sound absorption bandwidth in the 500-2000Hz range, demonstrating the non-obviousness of the parameter selection in this invention. However, when the ratio of the microslit length to the diameter of the circular hole is 1.2-1.8 (outside the scope of this invention), the microslit coverage area can completely encompass the circular hole outlet area. Sound waves diffuse uniformly into the microslit friction layer after resonance through the circular hole, forming a complete acoustic impedance match. When the ratio is too small (e.g., 1.0), the microslit does not adequately cover the sound flow at the circular hole outlet, and some sound energy escapes without frictional dissipation. When the ratio is too large (e.g., 2.17), acoustic crosstalk occurs between adjacent microslits, which weakens the independent resonance effect of a single hole-slit configuration.

[0091] 4.2 Verification of the correlation between hot rolling temperature and pressure

[0092] A fixed aluminum substrate 3003-H12, an aluminum film 3003, a film thickness of 0.2 mm, and a rolling speed of 1.5 m / min were used for hot rolling composite under different temperature and pressure combinations. The interfacial peel strength and the retention of micro-gap width tolerance after composite were tested. The results are shown in the table below.

[0093] Table 3: Verification Data Table of Correlation between Hot Rolling Temperature and Pressure

[0094] 320°C 25MPa 0.6MPa ±0.04mm Metallurgical bonding not formed, strength not up to standard 380°C 30MPa 1.8MPa ±0.04mm Excellent metallurgical bonding and good precision maintenance 440°C 35MPa 1.7MPa ±0.07mm The strength is acceptable, but the precision is slightly reduced. 480°C 40MPa 1.5MPa ±0.15mm Abnormal grain growth, exceeding precision standards

[0095] The results show that when the temperature is below 350°C, the oxide film on the aluminum surface is difficult to be fully destroyed, and the atomic diffusion at the interface is insufficient. Even with increased pressure, an effective metallurgical bond cannot be formed, and the peel strength is only 0.5-0.8 MPa. Under long-term vibration conditions (simulating rail transit conditions, vibration frequency 10-50 Hz, acceleration 2g, for 1000 hours), microcracks are prone to appear, resulting in a 3%-5% drift in the peak sound absorption frequency. When the temperature is above 450°C, the 0.1-0.3 mm thick aluminum film is prone to abnormal grain growth or even local burn-out. The edges of the microcracks undergo irregular deformation due to material softening, and the width tolerance deteriorates from ±0.04 mm to ±0.15 mm, exceeding the accuracy requirement of ±0.05 mm. Only the 350-450°C, 20-40MPa process window of this invention constitutes an inseparable and interconnected whole that guarantees an interfacial peel strength ≥1.5MPa and a micro-gap accuracy ≤±0.05mm. Within this window, the two form a synergistic optimal combination; neither can be omitted, constituting the optimal process combination. Beyond this range, strength and accuracy cannot be simultaneously achieved, demonstrating the creativity in the selection of process parameters.

[0096] In summary, the core process conditions of this invention are as follows: First, the hole and slot must be precisely aligned, with the positioning error controlled within 0.1 mm; otherwise, the acoustic coupling effect between the circular hole and the micro-slit will be significantly weakened. Second, the width of the micro-slit must be controlled between 0.2 and 0.8 mm, and the ratio of the micro-slit length to the diameter of the circular hole must be 1.2 to 1.8 to ensure acoustic impedance matching and broadband resonance superposition. Third, during the hot rolling composite process, the temperature and pressure must be controlled in a coordinated manner within the range of 350-450°C and 20-40 MPa; neither can be omitted. The above three process conditions are interrelated and work together, which are the key technologies for achieving the optimal synergistic effect of high sound absorption, high strength, and high precision.

[0097] Application example:

[0098] Taking the HVAC equipment control room at a station in Tianjin as an example, the room has an area of ​​approximately 80m² and a ceiling height of 4.5m, housing large HVAC pump sets and piping. Before the renovation, the following problems existed: the equipment generated low-frequency steady-state noise centered at 500Hz, with a reverberation time (T30) as long as 1.0s, severely affecting the clarity of voice commands during equipment maintenance; simultaneously, the original sound-absorbing ceiling used a rock wool-filled perforated aluminum panel structure, which, due to long-term vibration, experienced rock wool powdering and shedding, posing a potential dust pollution hazard.

[0099] Renovation plan: Remove the existing rock wool sound-absorbing ceiling and replace it with an aluminum-based microporous sound-absorbing structure (3.2mm thick, 7.8kg / m²) prepared according to Example 1 of this invention. This structure is directly fixed to the existing keel system using a snap-fit ​​method, eliminating the need for rock wool filling. The installation process requires no additional keel support, increasing construction efficiency by 50% compared to traditional solutions.

[0100] After the modification, on-site testing was conducted in accordance with GB / T 20247-2006 and ISO 3382.

[0101] (1) The reverberation time of 500Hz was reduced from 1.0s to 0.7s, and the reverberation time of 1000Hz was reduced from 0.9s to 0.65s, with a reduction of more than 30%; the noise level in the equipment operation area was reduced from 72dB(A) to 58dB(A), which meets the requirements of GB 50118-2010 "Code for Sound Insulation Design of Civil Buildings" for equipment rooms.

[0102] (2) The Speech Clarity Index (STI) improved from 0.45 to 0.68, reaching the "good" level, and staff did not need to raise their volume when communicating with each other.

[0103] (3) After 12 months of use, the product surface was found to be free of powdering, rust, and deformation. The sound absorption performance was not reduced and there was no dust pollution problem. The product was highly recognized by the station management department.

[0104] This application example demonstrates that the present invention has excellent acoustic performance, durability and ease of construction in practical engineering, and is particularly suitable for rail transit and industrial building fields that require fire prevention, dust prevention and vibration resistance.

[0105] The above description is merely a preferred embodiment of the present invention. It should be understood that the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. The present invention is not limited to the forms disclosed herein and should not be construed as excluding other embodiments, but can be used in various other combinations, modifications, and environments. Modifications and variations made by those skilled in the art that do not depart from the spirit and scope of the present invention should be within the protection scope of the appended claims.

Claims

1. A method for forming an aluminum-based microporous sound-absorbing structure, characterized in that: Includes the following steps: S1. Substrate processing: The first circular hole array (3) is processed on the 3 series aluminum alloy plate by CNC drilling process to form an aluminum substrate (1). After processing, the surface of the aluminum substrate (1) is polished. S2, Thin film processing: The second micro-slit array (4) is processed on the aluminum thin film (2) using ultraviolet laser processing equipment, and the laser power is adjusted according to the micro-slit width requirements; S3, Composite molding: The aluminum film (2) and the aluminum substrate (1) are precisely composited and fixed using an aluminum-based composite process to achieve metallurgical bonding, so that the second slit array (4) and the first circular hole array (3) are precisely aligned in position; S4. Post-treatment: The composite structure is subjected to surface anti-corrosion treatment to form an anodized anti-corrosion layer (5) and / or an anti-oxidation coating (6) on the surface. S5. Performance testing: Test the sound absorption coefficient of the finished product; if the test result does not meet the expected value, perform geometric dimension testing on the first circular hole array (3) and / or the second slit array (4), and compare the measured dimensions with the verified target tolerance range; adjust the CNC drilling process parameters and / or ultraviolet laser processing parameters in reverse according to the direction and magnitude of the dimension deviation to correct the processing error, and then repeat step S3 and subsequent steps until the sound absorption performance is qualified.

2. The method for forming an aluminum-based microporous sound-absorbing structure according to claim 1, characterized in that: In steps S1 and S2, a CCD vision positioning system is used to align the center position of the first circular hole array (3) with a positioning accuracy of ≤0.08mm to ensure the positional accuracy of processing and stacking.

3. The method for forming an aluminum-based microporous sound-absorbing structure according to claim 1, characterized in that: In step S3, the aluminum-based composite process is a hot-rolled composite method, which includes the following steps: S301. The bonding surfaces of the aluminum substrate (1) and the aluminum film (2) are subjected to plasma activation treatment. S302. By using positioning pins and alignment marks, the aluminum film (2) and the aluminum substrate (1) are precisely stacked to form a composite, with a positioning error ≤0.1mm. S303. The composite is fed into a hot rolling mill and rolled at a temperature of 350-450°C and a pressure of 20-40MPa. The hot rolling temperature and rolling pressure are complementary, so that the two metal interfaces can achieve metallurgical bonding. The interface peel strength after composite is ≥1.5MPa.

4. The method for forming an aluminum-based microporous sound-absorbing structure according to claim 1, characterized in that: In step S3, the aluminum-based composite process is an adhesive bonding method. The adhesive used is selected from one or more of the following: fire-resistant inorganic silicate adhesive, ceramic-based adhesive, or aluminum-based composite adhesive. The adhesive thickness is 0.03-0.08 mm, and the temperature resistance after bonding is ≥600℃.

5. The method for forming an aluminum-based microporous sound-absorbing structure according to claim 1, characterized in that: In step S4, the side of the aluminum substrate (1) facing away from the aluminum film (2) is anodized to form an anodized anti-corrosion layer (5). The anodizing process is sulfuric acid anodizing, the oxide layer thickness is 10-15μm, and the anti-corrosion level reaches C3 or above. The surface of the aluminum film (2) is provided with an anti-oxidation coating (6) with a thickness of 5-10μm. The anti-oxidation coating (6) is prepared by vacuum coating process and the material is aluminum oxide or aluminum nitride.

6. An aluminum-based microporous sound-absorbing structure prepared by the molding method of the aluminum-based microporous sound-absorbing structure as described in any one of claims 1-5, characterized in that: include: An aluminum substrate (1) is a 3-series aluminum alloy substrate, on which a first circular hole array (3) is provided through the thickness direction. An aluminum thin film (2) is an aluminum alloy film adapted to an aluminum substrate. A second micro-slit array (4) is provided on it, which extends through the thickness direction. The aluminum thin film (2) is covered and fixed on the upper surface of the aluminum substrate (1) by an aluminum-based composite process. The center of each hole in the first circular hole array (3) is aligned vertically with the center of each micro-slit in the second micro-slit array (4). The length of each micro-slit is not greater than the difference between the spacing and diameter of the corresponding hole in the first circular hole array (3) aligned vertically with it. In the wide frequency range of 500-2000Hz, a double-peak coupling effect is generated between the first circular hole array (3) and the second micro-slit array (4), and the sound absorption coefficient is ≥0.

75.

7. The aluminum-based microporous sound-absorbing structure according to claim 6, characterized in that: The aluminum substrate (1) has a substrate thickness of 2-5 mm, the aluminum film (2) has a thickness of 0.1-0.3 mm, and the arrangement spacing of the first circular hole array (3) is equal to the arrangement spacing of the second micro-slit array (4).

8. The aluminum-based microporous sound-absorbing structure according to claim 6, characterized in that: The circular holes in the first circular hole array (3) are periodically distributed in a square lattice. The diameter of the circular holes in the first circular hole array (3) is 2-4 mm, and the spacing between adjacent circular holes is 5-8 mm.

9. The aluminum-based microporous sound-absorbing structure according to claim 6, characterized in that: The microslits in the second microslit array (4) are arranged in parallel. The width of the microslits in the second microslit array (4) is 0.2-0.8 mm, and the length is 1.2-1.8 times the diameter of the circular holes in the first circular hole array (3). The second microslit array (4) is formed by ultraviolet laser processing. Material removal is achieved during the processing. The laser spot diameter is ≤0.05 mm, the processing speed is 10-30 mm / s, and the microslit width tolerance is ≤±0.05 mm.

10. The aluminum-based microporous sound-absorbing structure according to claim 6, characterized in that: The sound absorption coefficient is ≥0.75 in a wide frequency range of 500-2000Hz, of which the sound absorption coefficient at 500Hz is ≥0.9 and the noise reduction coefficient (NRC) is ≥0.

75. sound absorption coefficient The calculation formula is: ; In the formula: ; ; in, =1.84e -5 Pa·s is the air viscosity coefficient; t is the aluminum film thickness, in meters. denoted as the hydraulic diameter; a and b are the width and length of the microslit, respectively. The open area ratio is equal to the ratio of the open area to the total area. , is a dimensionless constant; Where f is the angular frequency, and f is a number ranging from 20 to 8000 Hz; air density; denoted as the speed of sound in air; D is the depth of the back cavity of the microporous sound-absorbing structure in meters; r is the acoustic resistance; and m is the acoustic mass.